Paradigm Shift Towards Practical Oriented Teaching Of Mathematics - Shankar, S. Prabu (Voices of Teachers and Teacher Educators, 2021)
This paper is aimed at highlighting the need for practical oriented teaching of mathematics for better conceptual understanding and improved mathematical problem solving ability among students studying at the high school level. This paper also attempts to inquire upon the teacher’s attitude, preparedness, the possibilities and the pros and cons of whether practical oriented teaching of mathematics is made possible. Gowers (2016) insists on the need to teach mathematics, as practically as a teacher can. In the process, a concept steadily unfolds creating better scope for understanding and problem solving among children. It has been accounted from the reviews and observations in the classroom context that the need to teach mathematics practically contributes in enhanced conceptual understanding and problem solving ability.